Perspective of tinalized microorganisms in the development of safe probiotics - Bomko, Tatyana; Martynov, Artur; Nosalskaya , Tatyana (Annals of Mechnikov's Institute, 2021)
Introduction: The use of probiotics is a common method of influencing the intestinal microbiota. But oral administration of live probiotic bacteria has significant disadvantages. First, live probiotic bacteria in gastrointestinal tract are exposed to acidic environment and gastric pepsin, then the destructive effects of bile acids and pancreatic enzymes. As a result, most microorganisms die, and the remaining ones are not always able to restore their number. There are also difficulties with the integration of surviving bacteria into the biofilms of the parietal microflora, which has protective antagonistic properties against exogenous microorganisms. In the case of survival of a significant part of the introduced microorganisms and their reproduction, one of the safety problems is the possibility of penetration of live bacteria from the intestine into the tissues and blood, with the occurrence of bacteremia, especially in patients with impaired epithelial barrier function. Another problem with the use of live probiotics is the possible transfer of antibiotic resistance genes by probiotic strains in the human digestive tract by horizontal gene transfer. In newborns, probiotics can interfere with normal bowel colonization. Rationale: In recent years, there has been interest in heat-killed probiotics, including through the use of tyndallization. But the viability of bacteria or the integrity of their cell wall is not an important condition for the intestinal effects of probiotics. There is a considerable amount of experimental in vitro and animal model studies that show that after heat treatment, bacterial extracts and supernatant in most cases retain their basic probiotic properties. Experimental evidence for the protective effect of various heat-killed probiotic bacteria against intestinal pathogens is presented. Thus, killed lactobacilli or their purified structures competed for adhesion sites at the gastrointestinal level with E. coli-ETEC, Campylobacter and H. pylori. In a model of salmonellosis in mice, heat-killed lactobacilli, alone or in combination, reduced pathogen invasion and inflammation. Oral administration of inactivated bifidobacteria to mice also resulted in increased resistance to Salmonella infection. In vitro heat-inactivated Bifidobacterium BB12 prevented the formation of Streptococcus mutans biofilms. Immunomodulatory effects of heat-killed probiotics have been found in both innate and acquired immunity. Effects such as induction of IL-12 secretion, stimulating effect on macrophages, enhancement of IgA production, etc. are given. Heat-killed probiotic bacteria help support the integrity of the intestinal barrier, which has been proven in a number of studies on intestinal cell monolayers (Caco-2 / TC7, HT29-MTX, CacoGoblet), as well as in studies in rats with acute alcoholic intestinal lesions. The effects of some active components of heat-killed bacteria are considered. The main components of the cell wall of gram-positive bacteria are peptidoglycans and lipoteichoic acids. They can be considered key components of the immunomodulatory action of most probiotics. Lipoteichoic acids of L. plantarum on cultures of dendritic cells of mice spleen showed the properties of an IL-12 inducer, had an anti-inflammatory effect on the lines of epithelial cells of the pigs intestine, inhibiting the induced field I:C production of IL-8. Peptidoglycan from L. rhamnosus improved the innate immune response in mice with weakened immunity after infection with S. pneumoniae. Peptidoglycans isolated from different species of Lactobacillus have the ability to inhibit the LPS-induced release of inflammatory cytokines in mice RAW 264.7 macrophage-like cells. Polysaccharide-peptidoglycan complexes from L. casei YIT9018 were active against L. monocytogenes and P. aeruginosa. A large amount of research has been devoted to the effects of exopolysaccharides isolated from Bifidobacterium and Lactobacillus strains in in vitro and in vivo experiments. Heat-killed Bifidobacterium longum BCRC 14634 or exopolysaccharides isolated from them increased the proliferation of J77A.1 macrophages and the secretion of the anti-inflammatory cytokine IL-10. Exopolysaccharides coagulate with pathogens, which reduces the availability of the latter to the intestinal epithelium, forming the films that protect intestinal cells from damage by pathogens or their toxins. In animal studies, probiotics strains that produce exopolysaccharides reduced intestinal colonization by pathogens compared to non-producing strains. Cell-free supernatants of probiotic bacteria contain a wide range of compounds with antimicrobial properties, including organic acids, hydrogen peroxide, reuterin and bacteriocins. They are also present in heat-inactivated probiotic products because they can withstand temperatures up to 100 ° C. A number of clinical data, including high-quality studies, on the efficacy of heat-killed probiotics are presented. 20-day use of tyndallized L. reuteri and B. breve with the polymer xyloglucan reduced the severity of the syndrome of excessive bacterial growth in the small intestine in adults diagnosed with functional bloating (double-blind randomized study). Tyndallized L. reuteri SGL01 and B. breve SGB01 reduced the duration of colic (crying attacks) in 46 infants. In a randomized controlled trial, tyndallized L. acidophilus HA122 with chamomile and melissa extracts significantly reduced the mean daily infant crying time compared to simethicone. Heat-killed L. acidophilus LB significantly reduced clinical symptoms in patients with chronic diarrhea, and the effect was superior to that of live lactobacilli. In a placebo-controlled study in children with acute diarrhea caused by rotavirus, lyophilized, heat-killed L. acidophilus LB significantly reduced the number of children with loose stools and significantly reduced the duration of diarrhea. In a randomized, double-blind, placebo-controlled clinical trial in children with persistent non-rotavirus diarrhea, the use of lyophilized, heat-killed bacteria L. acidophilus LB reduced the recovery time of normal stool. In a multicenter, randomized, double-blind, controlled study, the use of formula containing heat-killed B. breve C50 and S. thermophilus 065 in children at high risk of atopy reduced the incidence of digestive and respiratory allergic events. Recently, products containing various tyndallized probiotics strains have appeared on the market. These are L. reuteri, B. breve and xyloglucan for the treatment of colic in adults and children, L. acidophilus HA122 with extracts of chamomile and lemon balm for the treatment of colic in children, a complex of tyndalized lacto- and bifidobacteria with gelatinate tanat for the treatment of intestinal dysbacteriosis associated with diarrhea. Conclusion. Heat-killed probiotics are no less effective than live bacteria and have benefits such as greater safety, ease of standardization, transportation, and storage. They are an alternative to live probiotics and open up the possibility of using them to treat various diseases and conditions. DOI: 10.5281/zenodo.4657644